Analysis of High Order Thinking Skills (HOTS) in Objective Test Questions for Science Learning Material in Fourth Grade Elementary School - Putri, Nabila Eisa; Fatmawati, Laila (The Indonesian Institute of Science and Technology Research, 2024)
Test instruments are crucial assessment aspects for students, utilized to gauge their knowledge abilities during the learning process. Educators or teachers must scrutinize and analyze the tests beforehand to ensure that the questions predominantly assess higher-order thinking skills (HOTS). Learning processes predominantly focusing on lower-order thinking abilities may result in students struggling with questions that require higher-order thinking skills. This study aims to determine the percentage of knowledge dimension aspects, cognitive process dimension, and HOTS content in three supporting books for Science Learning Material in Fourth Grade. It adopts a quantitative descriptive research approach, analyzing a population of 400 multiple-choice questions from three supporting books, with a sample size of 400 questions. Data collection techniques involve observation and documentation methods, utilizing document analysis guideline sheets as instruments. Findings reveal that the percentage of knowledge dimension results across the three supporting books indicate: factual dimension (23.2%, 34%, and 42%), conceptual dimension (54.8%, 47%, and 40%), procedural dimension (19.6%, 16%, and 16%), and metacognitive dimension (2.4%, 3%, and 2%). Regarding cognitive process dimension and HOTS content (C4 to C6), the supporting books yield: remembering level (C1) ranging from 27.2% to 40%, understanding level (C2) ranging from 32.4% to 40%, applying level (C3) ranging from 8% to 12.8%, analyzing level (C4) ranging from 8% to 22%, evaluating level (C5) ranging from 3% to 7.2%, and creating level (C6) ranging from 0% to 1.6%. According to these findings, the three supporting books for Fourth Grade Elementary School Science Learning Material do not adequately meet the criteria for fostering higher-order thinking skills.